High bit-depth image compression with application to seismic data - Radosavljevic, Milos; Xiong, Zixiang; Lu, Ligang; Vukobratovic, Dejan (2016 Visual Communications and Image Processing (VCIP), 2016)
Inspired by the high performance of High Efficiency Video Coding (HEVC), this paper reports our work on applying the ideas of HEVC intra coding to compression of high-depth images such as 32 bits per pixel (b/p) seismic data. Compared to a licensed commercial wavelet-based codec that is currently used for seismic image compression, which performs on par with JPEG-XR, our new image codec significantly improves the PSNR vs. compression ratio performance. The codec's subject performance is rated by geologist as highly satisfactory.